(untitled) (Praxis Educativa, 2020)
Faced with a crisis of this nature, so dramatic, universal and resistant, I propose to analyze the most urgent and pressing challenges that this exceptional situation presents to the educational task. Facing the uncertainty, complexity and sophistication of such a universal system of relationships in which problems, possibilities and challenges of such an unpredictable, complex and immeasurable nature continually emerge require the development of individual and collective wisdom, that is, qualities and personal and social resources of a higher order, of a cognitive, emotional, ethical and social nature. For this purpose, it seems to me essential to unravel the complex, open and indeterminate nature of the mechanisms and processes of construction of the human subject, in the strange coordinates of this digital, global and pandemic era. What does it mean and how is the educational learning of knowledge, skills, attitudes, emotions and values promoted? How to understand the conscious reconstruction of the subconscious mechanisms that are acquired in everyday experience? A new pedagogical culture and another way of understanding the school as an institution makes its way with both necessity and urgency to seek the design of contexts, projects, relationships, forms of teaching and evaluating and ways of conceiving the truly “educational” teaching function, which accompany and provoke the possible development of autonomous, cultured and supportive individuals.